1995
DOI: 10.1136/bmj.310.6983.827
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic aspirin and risk of peptic ulcer bleeding

Abstract: Objective-To determine the risks of hospitalisation for bleeding peptic ulcer with -the current prophylactic aspirin regimens of 300 mg daily or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
334
1
28

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(371 citation statements)
references
References 24 publications
8
334
1
28
Order By: Relevance
“…Previous studies have consistently reported that no dose-response relationship exists for aspirin-related risk of GI ulcer or bleeding. 8,15,30 In clinical practice, all patients treated with clopidogrel receive 75 mg daily, and the figure thus also reflects the importance of treatment duration. Moreover, the groups continue to separate, thus supporting the importance of ischaemic heart disease as a risk factor for adverse GI events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently reported that no dose-response relationship exists for aspirin-related risk of GI ulcer or bleeding. 8,15,30 In clinical practice, all patients treated with clopidogrel receive 75 mg daily, and the figure thus also reflects the importance of treatment duration. Moreover, the groups continue to separate, thus supporting the importance of ischaemic heart disease as a risk factor for adverse GI events.…”
Section: Discussionmentioning
confidence: 99%
“…Studies often had the following exclusion criteria: cancer (n=10), oesophageal varices (n=10), Mallory-Weiss disease (n=10), alcoholism (n=7), chronic liver disease (n=7) or/and coagulopathies (n=6). Aspirin exposure was de®ned as use during the last week in nine studies, use in the last month in three studies, and use reaching the index date or prescriptions that would cover the index date in the other 1 2 De Abajo [58] 3 4 5 6 7 8 9 10 11 12 Sorensen [57] García Rodríguez [55] Pérez Gutthan [54] McMahon [52] Hallas [49] Cohorts Lanas [56] Wilcox [53] Matikainen [52] Kelly [51] Weil [48] Savage [47] Henry [46] Keating [45] Nobili [38] Holvoet [44] Laporte [43] Case/control 0 1 3 14 15 2.2 3.1 Figure 1 Relative risks and 95% con®dence interval reported in original publications on aspirin use and UGIC during 1990 ±2001, strati®ed by study design. ®ve studies.…”
Section: Methodological Factorsmentioning
confidence: 99%
“…However, the risk was still elevated for doses up to 300 mg day x1 . Studies reported a signi®cantly increased risk of UGIC with daily doses below 300 mg, [47,56] 150 mg [46,57], and even as low as 75 mg [48,58] (Table 3).…”
Section: Aspirin Use Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean annualized rate of ulcer complications is 3.0% per year, and we adopted this as our base-case estimate for average-risk patients in the NSAID NS strategy. The addition of low-dose aspirin (ASA) to an NSAID NS increases the risk of GI complications by 2.5 times baseline, on average (9,(25)(26)(27)(28)(29). We therefore assumed that the annualized rate of ulcer complications was 7.5% in the subset of patients receiving an NSAID NS ϩ ASA combination (3.0% base-case rate ϫ 2.5), and we varied this estimate between 5% and 10% in our sensitivity analysis.…”
mentioning
confidence: 99%